Optimalisasi Pemanfaatan Tanah Kas Desa dalam Meningkatkan Ekonomi Masyarakat - Olan Suparlan; Sugiyanto Sugiyanto; Muhammad Pengkuh Wedhono Jati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research examines how village treasury land is used to improve the economy of the people of Sukoreno Sentolo Kulon Progo Village. In the Regulation of the Governor of the Special Region of Yogyakarta Number 65 of 2013, TKD is a type of village wealth. Sukoreno is one of the sub-districts in Kulonprogo Regency, Yogyakarta Special Region. Similar to other sub-districts, Sukoreno also has TKD which originates from sultan land (belonging to the Sultanate of Yogyakarta. This research focuses on discussing how village treasury land is utilized to improve the community's economy. This type of research is descriptive qualitative research by selecting respondents using purposive sampling The data obtained is then explained using stage four, namely: 1) Data reduction, 2) Data presentation, 3) Drawing conclusions, and 4) Reliability and Validity. The informants in this research were the head of the Sukoreno subdistrict, the subdistrict welfare section, the TKD community. The results of the research found that in the use of TKD there were several practical points in which the use of village treasury land was not optimal, both in terms of operations and agricultural products, so other alternatives were needed in the use of village treasury land. The use of village treasury land in Sukoreno was originally used for agriculture. In Sukoreno Village, most of it was used for rice farming. The Sukoreno Village government policy then created an alternative use of village treasury land that was more varied, namely that the yard land was used to empower community groups through cultivating dairy goats and fattening sheep, as well as cultivating horticultural crops. The Sukoreno District Government realizes that more effective optimization is needed to improve the community, one of which is by planting benguk plants. In practice, the use of TKD in Sukoreno Village is in line with what is stated in the instructions from the Governor of the Special Region of Yogyakarta to maximize the use of village treasury land as stated in the Regulation of the Governor of the Special Region of Yogyakarta (DIY) Number 65 of 2013.